The new social policy - Cahill, Michael (Blackwell, 1994)
This student text introduces the main themes and issues of social policy. By examining a variety of social topics, such as leisure, work, media and information technology, the book explores the nature of inequality and the impact of social policy. It then considers the future for social policy, discussing three models of social welfare: the consumerism of the New Right; the citizenship of social democracy and the ecological perspective of the Green movement.